Technology-driven innovation in Gulf Cooperation Council (GCC) countries emerging research and opportunities - Visvizi, Anna 1976-; Bakry, Saad; Lytras, Miltiadis D. 1973-; Alhalabi, Wadee 1970- (IGI Global, 2019)
"This book demonstrates how technology-driven innovation in the Gulf Cooperation Council countries influences the evolution of the economic sustainability model in the region and how experiences drawn from this process may be employed across the field of international business and international business model innovation"--